Studi Kinerja Keuangan PT. Ace Hardware Indonesia dengan Analisis Laporan Keuangan - Delia Agustina; Fadhilah Fitria Sani; Altasya Nurmaeza; Agnes Indan; Hariany Idris (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
Evaluating the financial position of a company can be done by analyzing the company's financial statements. Understanding the financial position of a company through various analyzes including financial ratio analysis. The purpose of this research is to analyze the financial statements of PT. Ace Hardware Indonesia Tbk. Research Methods: The method used is technical analysis which consists of calculating the liquidity ratio and the company's solvency ratio. Financial data and information were obtained from PT Ace Hardware Indonesia Indonesia Stock Exchange for the economic period 2020-2021. From the calculation results, the research shows that the liquidity ratio and solvency ratio are both in good condition, which means the company can manage its finances well and pay its obligations according to maturity.